Effect of isoflavone-enriched soybean flour, zinc (Zn) and vitamin E in the ration on testosterone level and total permatogenic cell in seminiferous tubules of rat - ., Astuti; Muchtadi, D; Astawan, M; Purwantara, B; Wresdiyati, T (Indonesian Journal of Animal and Veterinary Sciences, 2008)
The objective of this experiment are to evaluate the effects of isoflavoneen-enriched soybean flour, zinc (Zn) and vitamin E on testosterone level of male rats and total spermatogenic cells in the seminiferous tubules of rat testes as animal model. Diet was given as isonitrogen and isocaloric with 15% of dietary protein. Thirty male Sprague Dawley rats were divided into six groups and treated with isoflavoneen-riched soybean flour, Zn and vitamin E in different combination. Isoflavoneen-riched soybean flour (3mg/day) was given by oral administration, whereas Zn and vitamin E were mixed wih the basic diet. The treatment was done for 2 month. Results indicated that complete treatment of isoflavoneen-riched soybean flour, Zn and vitamin E on male rats increased testosteron level and total spermatogenic cells in comparison with single treatment and the other combination. The best results showed in the group that given isoflavoneen-enriched soybean flour with diet containing both Zn and vitamin E i.e; testosteron level 3.49 ± 0.31 ng/ml; while the number of spermatogonia, spermatocytes, early spermatids, late spermatids, and total spermatogenic cells were 37.56 ± 4.48, 67 ± 4.72, 287.11 ± 31.75, 227.22 ± 29.78, and 618.89 ± 47.38, respectively. It was concluded that synergic interaction between isoflavoneen-enriched soybean flour, Zn and vitamin E increased testosteron level and total spermatogenic cells of rat testes.       Key Words: Isoflavone-Riched Soybean Flour, Zn, Vitamin E, Testosterone, Spermatogenic Cells